The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/hep.22070
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of action of interferon and ribavirin in chronic hepatitis C: Summary of a workshop

Abstract: The current recommended therapy for chronic hepatitis C is the combination of peginterferon and ribavirin, which results in a sustained clearance of hepatitis C virus (HCV) in at least half of patients. However, the mechanisms by which interferon alpha (IFN-α) and ribavirin act against HCV are not well defined. The importance of understanding the biological pathways, cellular effects, and antiviral activities of these agents is underscored by clinical observations that nonresponders frequently have little or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 71 publications
1
61
0
Order By: Relevance
“…74 Proposed mechanisms explaining the efficacy of ribavirin have included its role in driving mutational frequencies, decreasing viral synthesis, or as an immunologic enhancer. [90][91][92][93] The importance of ribavirin in delaying the emergence of drug resistance has also been well illustrated. In PROVE 2, viral breakthrough (defined as Ͼ1 log above HCV RNA nadir or increase to Ͼ100 IU/mL in patients with previous viral suppression) was much higher in the "no ribavirin" arm compared to the SOC and triple therapy arms (24% compared to 1% and 2%, respectively).…”
Section: Role Of Ribavirin With Stat-cmentioning
confidence: 99%
“…74 Proposed mechanisms explaining the efficacy of ribavirin have included its role in driving mutational frequencies, decreasing viral synthesis, or as an immunologic enhancer. [90][91][92][93] The importance of ribavirin in delaying the emergence of drug resistance has also been well illustrated. In PROVE 2, viral breakthrough (defined as Ͼ1 log above HCV RNA nadir or increase to Ͼ100 IU/mL in patients with previous viral suppression) was much higher in the "no ribavirin" arm compared to the SOC and triple therapy arms (24% compared to 1% and 2%, respectively).…”
Section: Role Of Ribavirin With Stat-cmentioning
confidence: 99%
“…In the present case, new onset of type 1 diabetes and recurrence of Graves' disease were observed following PEG-IFN-alpha plus ribavirin treatment for chronic hepatitis C. It is well known that autoimmune disorders develop following IFN treatment (5)(6)(7)(8). IFN has been reported to exert antitumor activity, cytostatic activity and immunoregulatory effects, and antiviral activity (3).…”
Section: Discussionmentioning
confidence: 81%
“…In addition, animals administered ribavirin show enhancement of autoimmune reaction (4). Thus, the combination of IFN and ribavirin may induce autoimmune-related disorders, type 1 diabetes, autoimmune thyroid disease, systemic lupus erythematosus (SLE), and rheumatoid arthritis (5)(6)(7)(8). Graves' disease and type 1 diabetes are considered in relation to organ-specific autoimmune disease.…”
Section: Introductionmentioning
confidence: 99%
“…This activation is not virus-specific, and genetic variants (both host and pathogen) allow for resistance and varied responses to treatment. Consensus opinion has suggested that the innate and adaptive immune responses, host genetic variables, genetic diversity of the virus, and clinical comorbidities (diabetes) may all account for the ineffectiveness of IFN/RBV in the treatment of HCV [23].…”
Section: Discussionmentioning
confidence: 99%